GUEVARISTS AND COMMUNISTS: DIALOGUES AND CONTROVERSIES OF AN IMPOSSIBLE ALLIANCE. REBUILDING THE LINK BETWEEN THE REVOLUTIONARY PARTY OF THE WORKERS-REVOLUTIONARY ARMY OF THE PEOPLE AND THE ARGENTINE COMMUNIST PARTY (1969-1975). - Stavale, Santiago (Revista de Historia Social y de las Mentalidades, 2022)
The 60s and 70s in Argentina saw a proliferation of important debates within the world of the left. This article exposes the debates, characterizations, polemics and bridges that took place between the Revolutionary Party of Workers-People's Revolutionary Army (PRT_ERP), a guerrilla organization and exponent of the new left, and the Argentine Communist Party, a representative of the left-traditional. To do so, we will look at the positions they took on the events of the period 1969-1975, such as the Cordobazo and the return of Peronism to government, that is, the public polemics and attempts at rapprochement that existed between the two, with emphasis on the different political fronts they sought to build.
Keywords: Revolutionary Party of Workers-People's Revolutionary Army; Argentine Communist Party; New left; Traditional left; Political History